Qualitative exploration of digital chatbot use in medical education: A pilot study. (August 2021) - Kaur, Anjuli; Singh, Sid; Chandan, Joht S; Robbins, Tim; Patel, Vinod
Purpose: During the coronavirus disease 2019 pandemic, face-to-face teaching has been severely disrupted and limited for medical students internationally. This study explores the views of medical students and academic medical staff regarding the suitability and limitations, of a bespoke chatbot tool to support medical education. Methods: Five focus groups, with a total of 16 participants, were recruited using a convenience sample. The participants included medical students across all year groups and academic staff. The pre-determined focus group topic guide explored how chatbots can augment existing teaching practices. A thematic analysis was conducted using the transcripts to determine key themes. Results: Thematic analysis identified five main themes: (1) chatbot use as a clinical simulation tool; (2) chatbot use as a revision tool; (3) differential usefulness by medical school year group; (4) standardisation of education and assessment; (5) challenges of use and implementation. Conclusions: Both staff and students have clear benefits from using chatbots in medical education. However, they documented possible limitations to their use. The creation of chatbots to support the medical curriculum should be further explored and urgently evaluated to assess their impact on medical students training both during and after the global pandemic.